NRT1.1-centered nitrate signaling in plants. (1st September 2020) - Maghiaoui, Amel; Gojon, Alain; Bach, Liên
Abstract: Plants need efficient nitrate (NO3 – ) sensing systems and sophisticated signaling pathways to develop a wide range of adaptive responses to external fluctuations of NO3 – supply. In Arabidopsis thaliana, numerous molecular regulators have been identified to participate in signaling pathways that respond specifically to NO3 – . In contrast, only a single NO3 – sensing system has been described to date, relying on the NRT1.1 (NPF6.3/CHL1) NO3 – transceptor. NRT1.1 governs a wide range of responses to NO3 –, from fast reprogramming of genome expression (the primary nitrate response) to longer-term developmental changes (effects on lateral root development). NRT1.1 appears to be at the center of a complex network of signaling pathways, involving numerous molecular players acting downstream and/or upstream of it. Interestingly, some of these regulators are involved in crosstalk with the signaling pathways of other nutrients, such as inorganic phosphate or potassium. Although NRT1.1-mediated NO3 – sensing and signaling has mostly been documented in Arabidopsis, recent evidence indicates that similar mechanisms involving NRT1.1 orthologues are operative in rice. This review aims to delineate how the NRT1.1 sensing system and the downstream/upstream transduction cascades are integrated to control both the expression of NO3 – -responsive genes and the induced plasticity of root development. Abstract : This review provides an overview of recent studies on NO3 – signaling in Arabidopsis and rice, with a focus on the functional relationships between the NRT1.1 sensor and other molecular players in NO3 – signaling.